2017
DOI: 10.1111/bph.13941
|View full text |Cite
|
Sign up to set email alerts
|

Brain serotoninergic nervous system is involved in bombesin‐induced frequent urination through brain 5‐HT7 receptors in rats

Abstract: Background and Purpose Psychological stress exacerbates symptoms of urinary bladder dysfunction; however, the underlying brain mechanisms are unclear. We have demonstrated that centrally administered bombesin, a stress‐related neuropeptide, facilitates the rat micturition reflex. Brain bombesin‐like peptides modulate the serotoninergic nervous system activity under stress conditions; therefore, we examined whether brain 5‐HT is involved in the bombesin‐induced increased frequency of urination in urethane‐anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In our study, PCPA‐induced acute depletion of brain serotonin suppressed the centrally administered BB‐induced ICI shortening (Fig. 2), and the BB‐induced response was attenuated by central pretreatment with SB269970 (5‐HT 7 receptor antagonist), showing that brain BB‐like peptides might be involved in the facilitation of micturition in rats through the brain serotoninergic nervous system/5‐HT 7 receptors 102 …”
Section: Possible Brain Molecules Related To Stress‐induced Effects On Urinary Function: Our Neuropharmacological Studiessupporting
confidence: 56%
See 2 more Smart Citations
“…In our study, PCPA‐induced acute depletion of brain serotonin suppressed the centrally administered BB‐induced ICI shortening (Fig. 2), and the BB‐induced response was attenuated by central pretreatment with SB269970 (5‐HT 7 receptor antagonist), showing that brain BB‐like peptides might be involved in the facilitation of micturition in rats through the brain serotoninergic nervous system/5‐HT 7 receptors 102 …”
Section: Possible Brain Molecules Related To Stress‐induced Effects On Urinary Function: Our Neuropharmacological Studiessupporting
confidence: 56%
“…2), and the BB-induced response was attenuated by central pretreatment with SB269970 (5-HT 7 receptor antagonist), showing that brain BB-like peptides might be involved in the facilitation of micturition in rats through the brain serotoninergic nervous system/5-HT 7 receptors. 102…”
Section: Bombesinmentioning
confidence: 99%
See 1 more Smart Citation
“…Data subjected to statistical analysis were from a group size of at least five. Additionally, the group size was determined according to the expected difference in a desired endpoint measurement from our preliminary experiment and the mean of the SDs reported in our previous reports (Kawamoto et al ., ; Shimizu et al ., ). Eight rats were excluded due to cannula misplacement as described above.…”
Section: Methodsmentioning
confidence: 97%
“…Cystometric studies were performed according to the methods previously reported. 19,22,23 Briefly, after the surgery described above, the bladder catheter was connected to a pressure transducer (DX-100; Nihon Koden, Tokyo, Japan) for measurements of intravesical pressure and to a syringe pump for intravesical instillation of sterile saline at a rate of 12 mL/h. Intravesical pressure was recorded using a PowerLab System (AD Instruments, Bella Vista, Australia).…”
Section: Continuous Cystometrymentioning
confidence: 99%